Landscape architecture and environmentalism in the expansion era for Australian universities: the work of Bruce Mackenzie and Associates - Saniga, Andre (International Planning History Society Proceedings, 2018)
The 1960s and 1970s were an era of expansion of the tertiary education sector internationally with entirely new universities developed at an unprecedented pace. In the Australian context, the quintessential start-up suburban campus was usually set within a greenfield site - typically on postagricultural land at the fringe of rapidly expanding suburbia. An effective role for landscape architecture often materialised from symbiotic relationships between architects, engineers, planners, horticulturalists, and others. A significant driver in shaping and enacting a clear vision for a distinctive quality of campus landscape came internal to university administration. Communities consisting of academic staff, administrative staff, and other interested and talented practitioners have been found to be crucial in defining a niche for landscape architects in campus design, marking a significant moment in the recognition and due regard that would be paid to a small but influential profession on the Australian scene. This paper records the themes that define the distinctive nature of the Australian condition. Focusing on campus designs by Bruce Mackenzie and Associates (BMA), the paper provides a preliminary assessment of the roles and influence of people, organisations, and events in the creation of the modern campus in Australia. It concludes that the most effective results were achieved when the landscape architect was engaged at the formative stages of campus development and had broad support inclusive of collaboration with other consultants and with university administrators and on-ground staff. A significant ingredient for success in achieving innovative results was found to be the existence within the university of communities of interested and engaged people with joint aims and ambitions for the creation of high quality campus landscapes, often in line with a culture of environmentalism. Such communities often go unheralded yet without their involvement the establishment of campus landscapes that celebrated the conservation of Australian indigenous plants and forms may not have been as readily achieved.